TANGGUNG GUGAT NOTARIS ATAS KETIDAKSESUAIAN HARGA TRANSAKSI JUAL BELI TANAH DAN BANGUNAN DENGAN HARGA SEBENARNYA - Hidayatulloh Adiansyah (President University, 2016)
Agreement on sale and purchase of land and buildings creates tax obligations for sellers and buyers. Under these conditions often the parties provide false information on the price of the transaction in the deed so that the obligation to pay taxes is also lower. In essence the Notary is merely writing in writing and the form of legal actions of the parties concerned so whether in this case the Notary is accountable for the incompatibility of the transaction price with the actual price. The author in this study wants to examine and analyze further about the validity of the Notary Deed that contains false information related to the transaction price and the notary's responsibility for the false statements of the parties to avoid tax obligations. The research method used is normative legal research, namely legal research carried out by examining library materials or secondary legal materials while the problem approach is carried out using a legal approach and conceptual approach. The existence of false information submitted by the parties does not result in the Notary Deed being canceled. The Notary Deed during its manufacture has fulfilled the formal aspects of making authentic deeds which have been stipulated in the UUJN, so that they remain valid and binding on the parties. The existence of false information in the Notary deed for the incompatibility of the sale and purchase transaction price to avoid tax obligations is not the responsibility and responsibility of the Notary but is fully the responsibility and accountability of the parties because the Notary function only constructs the will of the parties.